E-governance as mechanism to rationalize the public service in Algeria - kada ben abdelah, nawel (Journal of Social Sciences and Humanities, 2020)
The bulk of the reforms that Algeria initiated to improve its public services came, albeit by a few, with a set of positive results that flow into the framework of modernizing public administration. Looking back a little, we find that the administration was floundering in a group of deviations and problems that prevented its development and promotion, and therefore the Algerian state baptized To adopt a set of reforms and consider them as a savior of public administration, the most prominent of which is the creation of the public facility in light of the reliance on information and communications technology, whichis included under the Algeria Electronic Project 2013. Within the framework of this research paper, we have tried to shed light on the reality of the application of electronic management and the changes that it brought about in the Algerian public administration. Through which we seek to identify the environment of the Algerian administration, which was characterized by a set of negative phenomena that led to the spreading of the relationship between them and the Algerian citizen and aversion to it through Lack of confidence in it. Where this study concluded through our evaluation of this experiment that there are a set of obstacles that prevented the success of this project, among which are the limited spread of the Internet, electronic illiteracy, resistance to change and lack of competencies, etc. This is what we will try to address in this research paper.